Transformasi Kebijakan Pidana Siber Menuju Keamanan dan Keadilan Digital - Fatri Sagita; Ardiansyah; Noercholis Rafid. A (Prosiding SISFOTEK, 2025)
This study examines the effectiveness of Indonesia’s criminal law in addressing cybersecurity and personal data protection amid the rise of artificial intelligence (AI). Using a normative juridical method with statutory and conceptual approaches, the analysis examines the Electronic Information and Transactions Law (Law No. 11 of 2008) and the Personal Data Protection Law (Law No. 27 of 2022), supported by secondary data from legislation, scholarly works, and official reports. The findings show that the criminal law framework remains fragmented, reactive, and unprepared for AI-driven cyber offenses. Overlapping institutional authority, the absence of an independent supervisory body, and limited digital forensic capacity undermine enforcement and legal certainty. Normatively, the study concludes that reforming Indonesia’s cyber penal policy is essential to extend criminal liability to algorithmic offenses, establish an independent supervisory authority, and integrate national digital forensic systems. Such reforms align with the principle of criminal law as ultima ratio, ensuring justice, security, and protection of citizens’ digital rights.